2009
DOI: 10.4064/sm194-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Local spectrum and local spectral radius of an operator at a fixed vector

Abstract: Abstract. Let X be a complex Banach space and e ∈ X a nonzero vector. Then the set of all operators T ∈ L(X) with σT (e) = σ δ (T ), respectively rT (e) = r(T ), is residual. This is an analogy to the well known result for a fixed operator and variable vector. The results are then used to characterize linear mappings preserving the local spectrum (or local spectral radius) at a fixed vector e.1. Introduction. Let X be a complex Banach space and let L(X) be the Banach algebra of all bounded linear operators on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…They showed that if ϕ : B(X) → B(X) is additive such that σ ϕ(T ) (x) = σ T (x) for all T ∈ B(X) and for all x ∈ X, then ϕ is the identity on B(X). Fixing a non-zero vector e ∈ X, the surjective linear mappings ϕ : B(X) → B(X) such that r ϕ(T ) (e) = r T (e) for all T ∈ L(X) were characterized in [5]. Different versions of this result in the case when X is finite-dimensional were considered in [7] and [3].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…They showed that if ϕ : B(X) → B(X) is additive such that σ ϕ(T ) (x) = σ T (x) for all T ∈ B(X) and for all x ∈ X, then ϕ is the identity on B(X). Fixing a non-zero vector e ∈ X, the surjective linear mappings ϕ : B(X) → B(X) such that r ϕ(T ) (e) = r T (e) for all T ∈ L(X) were characterized in [5]. Different versions of this result in the case when X is finite-dimensional were considered in [7] and [3].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Also, surjective linear mappings ϕ : L (X) → L (X) such that r ϕ(T ) (e) = r T (e) for all T ∈ L (X) were characterized in [3]. These results were generalized to the infinite-dimensional case in [5]. Since the inclusions ∂σ (T ) ⊆ σ δ (e) ⊆ σ (T ) always hold, this implies that {T ∈ L (X) : r T (e) = r (T )} is also residual in L (X).…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Since the inclusions ∂σ (T ) ⊆ σ δ (e) ⊆ σ (T ) always hold, this implies that {T ∈ L (X) : r T (e) = r (T )} is also residual in L (X). This is used in [5] in order to prove that, under the hypothesis of Theorem 1.1, the continuity of ϕ implies that it is a surjective spectral radius preserver, and therefore of a standard form [6]. It is asked in [5,Problem 3.5] whether the continuity assumption on ϕ may be removed from the statement of Theorem 1.1.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bračič and V. Müller in [7] characterized the surjective linear map φ : B(X) → B(X) satisfies r T (x) = r φ(T ) (x) for all T ∈ B(X) and x is a nonzero vector fixed in X. Different versions of this result in the case when X is finitedimensional were considered in [4].…”
Section: Introductionmentioning
confidence: 99%